Ingegneri & Ingegneria a Firenze In occasione dei 50 anni (dal 1970-71 al 2020-21) degli studi di Ingegneria presso l'Ateneo fiorentino - Angotti, Franco; Frosali, Giovanni; Pelosi, Giuseppe; Pierini, Marco (Dialoghi con la società, 2021)
This volume takes up part of the content of the one published on the occasion of the 40th anniversary of the foundation of the Faculty of Engineering of the University of Florence and constitutes, after 10 years, only for the first and second part of that volume, the natural continuation with all the necessary updates, while the third part will be resumed in a new volume. These 10 years have been characterized by a reform of the University which has significantly changed its structure with the abolition of the Faculties and the transfer of teaching organization to the Departments which, as it is well known, were originally constituted only as research bodies. This evolution will be discussed in the new volume.